The Longzhou Zhuang Brocade: Evaluation of the Tactile Sensation of Machine-Woven and Handmade Fabrics - Luo, Yongteng; Wechkama, Thitisak (Journal of Roi Kaensarn Academi, 2024)
Zhuang brocade is an exquisite handicraft prevalent in Guangxi Zhuang Autonomous Region, known for its unique pattern design, rich colors, and exquisite weaving techniques. People often struggle to distinguish the tactile differences between machine-woven and handmade fabrics when purchasing. The objective of this study is to investigate the differences in tactile characteristics between machine-woven and handmade Zhuang brocade. To achieve this, a mixed-methods approach combining qualitative and quantitative research was employed to collect and analyze quantitative data. A total of 14 samples, each measuring 20 cm × 20 cm, were selected, with 7 machine-woven and 7 handmade Zhuang brocade samples. Twenty-three experienced weavers with extensive knowledge of Zhuang brocade weaving were invited as evaluators to subjectively assess six tactile indicators: thickness、softness、velvet feel、fineness、smoothness、elasticity .The experiment was conducted under standard atmospheric conditions (temperature of 20±2°C and relative humidity of 65%±2%) to ensure the accuracy and reliability of the evaluation results. Tools used included an evaluation guide, two standardized evaluation forms, and a laboratory with constant temperature and humidity. In terms of data collection, the sources of this study mainly comprised tactile evaluation experiments, academic papers, interview results, and non-scaled questionnaires. Data processing was performed using Microsoft Excel, and the collected data were analyzed using descriptive statistics and hypothesis testing methods. The research findings indicate that handmade Zhuang brocade significantly outperforms machine-woven Zhuang brocade in terms of softness, elasticity, delicacy, thickness, and nap. Based on these findings, specific recommendations are provided for different stakeholders, including encouraging consumers to choose Zhuang brocade products based on personal needs and budget, and advising producers to focus on quality improvement and product innovation.